DA RECODIFICAÇÃO DO DIREITO PROCESSUAL CIVIL BRASILEIRO: ANÁLISE CRÍTICO EVOLUTIVA DOS DIPLOMAS PROCESSUAIS CIVIS (Revista Paradigma, 2020)
This article aims to analyze the codification of Brazilian civil procedurallaw from the elaboration of the Brazilian civil procedure code of 1939,through the 1973 procedural diploma, and its reforms, until reaching the current stage of national civilistic proceduralism, in it is also important to understand the legislative passages of the 2015 CPC.The aim is therefore to inquire whether or not there was legitimacy in the constructionof such procedural diplomas, which would certainly lead to the existence of a civil procedurallaw with a high burden of democratic legitimacy and less interference of theJurisdictional Function in controlling the elaborate laws.